South Asia Nutrition Knowledge Initiative: Abstract digest June 2024 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
In this second edition of South Asia Nutrition Knowledge Initiative’s Abstract Digest, we present insights from new global evidence on the double burden of underweight and obesity, interventions to improve women's diets, policy challenges related to unhealthy food and beverage marketing to children, and facilitators and barriers to implementing community-based interventions for addressing acute malnutrition in in low and middle-income countries.